Gut microbiome diversity and composition is associated with hypertension in women. Issue 9 (September 2021) - Louca, Panayiotis; Nogal, Ana; Wells, Philippa M.; Asnicar, Francesco; Wolf, Jonathan; Steves, Claire J.; Spector, Tim D.; Segata, Nicola; Berry, Sarah E.; Valdes, Ana M.; Menni, Cristina
Abstract : Objectives: Animal studies support a role for the gut microbiota in hypertension development, but large human studies are lacking. Here, we investigated the relationship between hypertension prevalence and gut microbial composition in two cohorts. Methods: We included 871 unrelated TwinsUK women with faecal microbiome data (16s rRNA gene sequencing). Multivariable linear models adjusted for age, age 2 and BMI as well as MiRKAT models, were used to estimate the association of hypertension with alpha- and beta-diversity metrics. To identify taxa associated with hypertension, a generalized additive model for location scale and shape was computed adjusting for covariates and multiple testing. Results were replicated in 448 women from PREDICT-1. Results: We found that measures of alpha diversity are significantly lower in hypertensive cases [Beta(95% confidence interval, 95% CI) = −0.05 (−0.095 to −0.004), P  = 0.03] and a significant association between beta diversity and hypertension (FDR < 0.05). We identified and replicated two genera associated with hypertension. The genus, Ruminiclostridium 6 was less abundant in hypertension cases [meta-analysis (95% CI) = −0.31 (−0.5 to −0.13), P  = 1 × 10 −3 ]. The uncultured microbe Erysipelotrichacea-UCG003 was more abundant in hypertensive cases [meta-analysis (95% CI) = 0.46 (0.3–0.62), P  = 1 × 10 −4 ]. We genomically analysed the 16 s rRNA sequence and established a 100% identity match with the 16 s rRNA sequence of the genus Faecalibacillus. We functionally annotated Ruminiclostridium, identifying 83 metabolic pathways, including pathways previously linked to blood pressure regulation. Conclusion: In this large human observation, we show that gut microbiome diversity and composition are associated with hypertension. Our results suggest that targeting the microbiome may be a novel means to prevent or treat hypertension. Abstract : Supplemental Digital Content is available in the text